Determinantes do desperdício de alimentos em restaurantes universitários: evidências empíricas a partir de fatores explicativos do comensal, do ambiente e do alimento - Porto, Fernanda (2025)
Food waste is a global phenomenon. A significant amount of food is wasted every year, and this has become a priority issue in international agendas, given its environmental, social, and economic impacts. This process occurs in several phases of the food chain. Food waste in the consumer food service sector is particularly significant. This sector is an important potential source of solid residue, demanding special attention due to the environmental, social, and economic impacts observed in this process. The development of practical actions to reduce food waste in public services can result in not only budget savings but also environmental benefits. In this context, this paper identified the main reasons that lead diners at a university restaurant commit food waste and examines the relationships among these reasons.. After a Literature Review, it was able to identify some reasons that drive customers to food waste. Subsequently, an analytical framework was proposed to measure these drivers empirically. During field data collection, research was conducted with 421 students who use the cafeteria at Mato Grosso Federal University. The techniques of data analysis chosen were Structural Equation Modeling and the Kruskal-Wallis Test. Results confirmed 12 out of 19 tested hypothesis. Statistical analyses confirm twelve of the nineteen hypotheses tested in research on the topic. The results revealed that food waste in university restaurants does not stem from isolated factors, but from a complex network of factorswhethr related to the diner, the environment, or the food. Intrinsic human factors such as behavioral intention and self-awareness showed a more direct relationship with wasted food waste than factors related to the environment or the food. The results suggest a change in the current approach used for campaigns and policies to reduce food waste in canteens.